Adsorption of Congo Red onto Humic Acid Isolated from Peat Soil Gambut Regency, South Kalimantan - Umaningrum, Dewi; Nurmasari, Radna; Santoso, Uripto Trisno; Astuti, Maria Dewi; Pradita, Hapsari Tyas (Universitas Jenderal Soedirman, 2023)
Humic acid is one of the green materials for wastewater treatment including for removal dyes as an adsorbent. Humic acid was isolated from peat soil, Gambut Regency, South Kalimantan following International Humic Substances Society method, and used to adsorb Congo red. The adsorption process was carried out in a batch system and the effect of pH, contact time, and adsorption capacity of Congo red on humic acid were studied. The adsorbent characterization by using FTIR. The results showed that the adsorption of Congo red on humic acid occurred at the optimum pH of pH 6, the optimum contact time was 120 minutes. The adsorption capacity of Congo red onto humic acid of 33.33 mg/g and follows the Langmuir model with R2 = 0.9926. The characterization of humic acid functional groups before and after adsorption of Congo red showed that the signal at 1,712.79 cm-1 were shifted to 1,705.07 cm-1 and 1,273.02 cm-1 were shifted to 1,265.30 cm-1. These suggested that the mechanism interaction was the electrostatic interaction between -NH3+ functional group of Congo red group and -COO- functional group of humic acid. It means that humic acid isolated from peat soil could be used as an adsorbent for the removal Congo red.